Knowledge of safe sex and sexually transmitted infections among high school students, Vientiane Prefecture, Lao PDR. Issue 2 (30th July 2020) - Inthavong, Khonesavanh; Ha, Le Thi Hai; Anh, Le Thi Kim; Sychareun, Vanphanom
ABSTRACT: Background: Adolescent knowledge of safe sex and sexually transmitted infections (STIs) can reduce the risk of STIs as well as unplanned pregnancies. Objective: To describe the knowledge of safe sex and STIs and to identify related factors among high school students in Vientiane Prefecture, Lao PDR. Method: This was an analytical cross-sectional study conducted at one high school from January to February 2019. A self-administered questionnaire was used to collect information from respondents. The questionnaires were completed by 337 respondents who were selected by stratified random sampling. The data collected were entered into and analysed using EpiData and Stata 13.0 software. Descriptive and inferential statistics were applied to determine the factors associated with knowledge of safe sex and STIs. Results: The results showed that nearly half of the participants (49.5%) had a good knowledge of safe sex and 51.9% of the respondents had a good knowledge of STIs. Significant positive associations were shown between knowledge of safe sex by students living with other people, those who had studied family planning and had religious beliefs reflecting acceptance to using birth control. Other factors positively associated with knowledge of STIs were students being in Grade 10, and who had studied STIs including HIV/AIDS. Conclusion: In this study, approximately half of the participants were aware of safe sex and had knowledge of STIs. There is a need to have comprehensive sexual education, particularly emphasising family planning, STIs, and HIV/AIDS for all grades in school.